Prevalence of impacted teeth on radiography in the Radiology Department of RSGMP Hasanuddin University in 2023: Prevalensi gigi impaksi pada radiografi di Departemen Radiologi RSGMP Universitas Hasanuddin tahun 2023 - Barunawaty Yunus; Khezi Yentissa Putri Abadi (Makassar Dental Journal, 2024)
Impaction occurs due to a mismatch between the size and shape of the teeth and the jaw. Generally, teeth that often experience impaction are posterior teeth, although anterior teeth can also experience impaction, but rarely found. This study was intended to determine the prevalence of tooth impaction on radiographs in the Radiology Department of RSGMP Hasanuddin University in 2023. This descriptive observational study used a total sampling design whose population was all panoramic radiographs of pa-tients with impacted teeth from medical report data in 2023. A total of 530 samples had impaction, 390 (73.5%) third molar im-paction, 50 (9.43%) premolar impaction, and 95 (17.93%) canine impaction. It was concluded that the more common impacted tooth in Unhas RSGMP in 2023 was the lower third molar.